Edukasi Kesehatan Pencegahan Anemia dengan Mengkonsumsi Buah Naga dan Madu pada Remaja Putri di SMAIT Al-Azhar Kota Jambi - Nurbaiti Nurbaiti; Laida Sanilpa Tiwi; Melda Amalia (Jurnal Abdimas Kesehatan (JAK), 2023)
Anemia is a condition in which the number and size of red blood cells or hemoglobin levels are below the threshold value for women less than 12.0 g. Anemia can be caused by a lack of iron intake, poor lifestyle such as smoking, drinking alcohol and breakfast habits, signs of anemia symptoms, headache, fatigue, frequent drowsiness, weakness and decreased concentration so that anemia does not occur, it is necessary to do prevention activities such as eating nutritious food, the purpose of this community service activity is to provide health education to young women at SMAIT Al-Azhar Jambi City so that young people know and understand about prevention of anemia, one of which is by consuming dragon fruit and honey, this activity is carried out on August 23, 2022 took place at the Al-Azhar mosque, Jambi City, which was attended by 75 young women, using lecture, discussion and question and answer methods, the media used were in the form of leaflets, infocus and laptops and power points, meeting time+ 90 minutes. At the implementation stage, before and after giving the material, an evaluation of the knowledge of young women throughpretest with the results of 33.33% good knowledge of young women and 66.66% knowledgeable enough, then inposttestit was found that the results of knowledge of young women increased to 100% good knowledge.HAs a result of this activity, young women understand and understand the prevention of anemia by consuming dragon fruit and honey.